Spectral method in the quantum theory of axial channeling - Shul'ga, N.F.; Syshchenko, V.V.; Neryabova, V.S. (Вопросы атомной науки и техники, 2014)
The quantization of the transverse motion energy in the continuous potentials of atomic strings and planes can take place under passage of fast charged particles through crystals. The energy levels for electron moving in axial channeling regime in a system of parallel [110] atomic strings of a silicon crystal are found for the electron energy of order of several hundreds of MeV, when a total number of energy levels becomes large. High resolution of the spectral method permits its usage for investigation of quantum chaos problem. При прохождении быстрых заряженных частиц через кристалл может иметь место квантование энергии поперечного движения в непрерывных потенциалах атомных цепочек и плоскостей. Найдены уровни энергии электрона, движущегося в режиме аксиального каналирования в системе параллельных цепочек [110] кристалла кремния, для случая электрона с энергией порядка нескольких сотен МэВ, когда число уровней энергии становится велико. Высокая разрешающая способность метода позволяет использовать его для исследования проблемы квантового хаоса. При проходженнi швидких заряджених часток крiзь кристал може бути наявним квантування енергiї поперечного руху в неперервних потенцiалах атомних ланцюжкiв та площин. Виявлено рiвнi енергiї електрона, що рухається у режимi аксiального каналювання у системi паралельних ланцюжкiв [110] кристала кремнiю, для випадка електрона з енергiєю близько кiлькох сотень МеВ, коли число рiвнiв енергiї стає великим. Висока роздiльна здатнiсть методу дозволяє використовувати його для дослiдження проблеми квантового хаосу.